Youth and revolution in Tunisia - Honwana, Alcinda Manuel (African arguments, 2013)
"The uprising in Tunisia has come to be seen as the first true revolution of the twenty-first century, one that kick-started the Arab Spring. In this remarkable work, Alcinda Honwana goes beyond superficial accounts of what occurred to explore the defining role of the country's youth, and in particular the cyber activist. Drawing on the testimony of those who shaped events, the book details the experiences of young activists both through the revolution and after the fall of the Ben Ali regime. An essential account of an event that has inspired the world, and its potential repercussions for the Middle East, Africa and beyond."--Page [4] of cover